MODEL OF PUBLIC-PRIVATE PARTNERSHIP IN THE SECTOR OF TOURISM (Scientific electronic journal "Labor Economics and Human Capital", 2023)
Tourism is characterized as being a sector that stands out as one of the business activities with the greatest potential for worldwide expansion, and as an engine for economic growth. If at the national level, the appeal of tourism is significant, on the local level this sector presents itself as an essential tool in regional development, as a means to avoid regional desertification and stagnation, stimulating the potential of more undeveloped regions. In such a competitive sector as tourism, companies should develop synergies and achieve competitive advantage. In this context, public-private partnerships play an important role in regional development. The aim of this paper is to present a theoretical context that combines different concepts and elements to explain and understand the public-private partnership phenomenon in tourism. A conceptual model of the role of public-private partnerships will be proposed in order to contribute to successful regional development.
Keywords: partnerships, public-private interface, regional development, conceptual model, tourism.